A hollow carbon@zinc sulfide negative electrode material for potassium ion battery and its preparation method and application

By using hollow carbon @ zinc sulfide negative electrode material in potassium ion batteries, the problem of insufficient performance of existing potassium ion battery negative electrode materials in high temperature environments is solved, and high specific capacity, excellent rate performance and high cycle stability are achieved. It is suitable for Potassium ion battery application under high temperature conditions.

CN118412451BActive Publication Date: 2025-02-18JINAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410498801.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2025-02-18
Estimated Expiration
2044-04-24

AI Technical Summary

Technical Problem

The existing potassium ion battery anode materials show low specific capacity, insufficient rate performance and rapid cycle attenuation in high temperature environments, making it difficult to meet the high-efficiency potassium storage needs under high temperature conditions.

Method used

Using hollow carbon @ zinc sulfide negative electrode material, hollow carbon @ zinc sulfide nanoparticles with highly controllable shell thickness were prepared through selective etching and vulcanization processes, and the negative electrode material for potassium ion batteries.

Benefits of technology

Significantly improve the rate performance, cycle performance and reversible capacity of potassium ion batteries under normal temperature and high temperature conditions. The reversible specific capacity of hollow carbon @ zinc sulfide nanoparticles with a shell thickness of 60nm is as high as 415mAh g-1 at room temperature, and at high temperature of 60℃ The reversible specific capacity is up to 450mAh g-1, and the cycle stability and rate performance are better than existing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118412451B_ABST
    Figure CN118412451B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of potassium ion battery materials, and relates to a hollow carbon @ zinc sulfide negative electrode material for potassium ion batteries, and a preparation method and application thereof. The present invention uses a tannic acid methanol solution to selectively etch ZIF-8 nanoparticles to obtain core-shell-zeolite imidazole framework @ coordination polymer nanoparticles, and then uses thioacetamide vulcanization to obtain hollow-tannic acid @ zinc sulfide nanoparticles, and finally obtains a hollow carbon @ zinc sulfide negative electrode material by heat treatment under an inert atmosphere, which is then applied to potassium ion batteries, and can effectively improve the specific capacity, rate performance and cycle performance of potassium ion batteries under normal temperature and high temperature conditions, and the material preparation method does not need to add a template, the process is simple, the reaction conditions are mild, and the shell thickness can be accurately controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of potassium ion battery materials, and in particular to a hollow carbon@zinc sulfide negative electrode material for a potassium ion battery, and a preparation method and application thereof. Background Art

[0002] At present, lithium-ion batteries have been widely used in many fields such as electric vehicles and electronic products. However, the limited and uneven distribution of lithium resources in the earth's crust has caused people to worry about the sustainable development of lithium-ion batteries. Potassium-ion batteries have the advantages of abundant resources and low cost; potassium-ion batteries are expected to become an important supplement to secondary battery technology and be used in important fields such as low-speed electric vehicles and large-scale energy storage. However, compared with the radius of lithium ions, Potassium ions have a larger ionic radius The volume of the negative electrode material is much larger, which makes the diffusion kinetics of potassium ions slow; in addition, the embedding of potassium ions into the negative electrode material will cause a large volume expansion, affecting the stability of the electrode. Especially in high temperature environments (such as 60°C), the structure and chemical stability of the negative electrode material will be affected, resulting in faster performance decay. Therefore, the development of high-specific-capacity potassium-ion battery negative electrode materials, especially high-specific-capacity potassium-ion battery negative electrode materials suitable for high-temperature environments, is still a huge challenge. A Chinese patent (CN113948699A) discloses a MOF-5 containing three carboxyl functional groups for high-temperature potassium-ion battery negative electrode materials, but its reversible specific capacity is low (<300mAh g -1 ), insufficient rate performance (1.0Ag -1 The specific capacity under the condition is less than 150 mAh g -1 ), and the cycle decay is fast. Developing a high-temperature potassium ion battery negative electrode material that takes into account cycle stability, high specific capacity, and high rate performance is very important to promote the development of high-temperature potassium ion batteries, but it has not yet been achieved.

[0003] Metal sulfides have attracted widespread attention as negative electrode materials for alkali metal ions due to their advantages such as high theoretical specific capacity, variable and adjustable structure, and rich material variety. However, metal sulfides as electrode materials will undergo large volume and structural changes, which will cause the active materials to fail and the capacity to decay rapidly; secondly, the metal sulfides themselves have poor electrical conductivity, which makes the ion / electron diffusion kinetics slow. Carbon-metal sulfide complexes with hollow structures are expected to solve the above-mentioned stability and kinetic problems. However, the performance of hollow structured electrode materials is often closely related to the shell structure of the hollow material (especially the shell thickness). However, the current lack of efficient synthesis and precise control of the synthesis method of hollow metal sulfide shell structure has hindered the application of hollow carbon-metal sulfide complexes in potassium ion batteries. Summary of the invention

[0004] The purpose of the present invention is to provide a hollow carbon@zinc sulfide negative electrode material for potassium ion batteries and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is to provide a method for preparing a hollow carbon@zinc sulfide negative electrode material for a potassium ion battery, the steps comprising:

[0007] The zeolite imidazole framework (ZIF-8) nanoparticles were selectively etched using tannic acid methanol solution to obtain core-shell-zeolite imidazole framework@coordination polymer nanoparticles;

[0008] The core-shell-zeolite imidazole framework@coordination polymer nanoparticles are vulcanized with thioacetamide to obtain hollow-tannic acid@zinc sulfide nanoparticles;

[0009] The hollow-tannic acid@zinc sulfide nanoparticles are subjected to heat treatment under an inert atmosphere to obtain the hollow carbon@zinc sulfide negative electrode material.

[0010] Furthermore, the concentration of the tannic acid methanol solution is 1.45-11.64 mM.

[0011] Furthermore, the mass ratio of the tannic acid to the zeolite imidazole framework (ZIF-8) nanoparticles is 1.25 to 10:1.

[0012] In the present invention, during the selective etching process, tannic acid forms a coating layer on the surface of ZIF-8 and releases protons to etch the inner layer of ZIF-8, thereby forming a yolk-eggshell structure, which can be regulated by controlling the concentration of tannic acid.

[0013] Furthermore, the mass ratio of the thioacetamide to the core-shell-zeolite imidazole framework@coordination polymer nanoparticles is 0.5 to 2:1.

[0014] Furthermore, the vulcanization temperature is 80-120°C, preferably 90°C.

[0015] Furthermore, the inert atmosphere includes: one of a nitrogen atmosphere, an argon atmosphere or a helium atmosphere, preferably an argon atmosphere.

[0016] Furthermore, the heat treatment temperature is 400-900° C., the heating rate is 1-20° C. / min, and the heat preservation time is 1-10 h.

[0017] Preferably, the heat treatment temperature is 500° C., the heating rate is 5° C. / min, and the holding time is 5 h.

[0018] Furthermore, the particle size of the hollow carbon@zinc sulfide nanoparticles is 300-800 nm, and the shell thickness is 45-90 nm.

[0019] The second technical solution of the present invention is to provide a hollow carbon@zinc sulfide negative electrode material prepared by the above preparation method.

[0020] The third technical solution of the present invention is to provide an application of the above hollow carbon@zinc sulfide negative electrode material in a potassium ion battery.

[0021] The hollow carbon@zinc sulfide negative electrode material prepared by the present invention can effectively improve the rate performance, cycle performance and reversible capacity of potassium ion batteries under room temperature and high temperature conditions.

[0022] Technical solution 4 of the present invention: provides a potassium ion battery negative electrode, the raw materials of which include the above-mentioned hollow carbon@zinc sulfide negative electrode material.

[0023] Furthermore, the potassium ion battery negative electrode raw materials include: a conductive agent, a binder and the above-mentioned hollow carbon@zinc sulfide negative electrode material.

[0024] Preferably, the conductive agent includes: one of conductive carbon black (Super P), acetylene black (Acetylene Black) or carbon nanotube (CNT), more preferably conductive carbon black (Super P).

[0025] Preferably, the adhesive comprises: sodium carboxymethyl cellulose and styrene-butadiene rubber mixed in equal weight ratio, or polyacrylic acid, or polyvinylidene fluoride, more preferably sodium carboxymethyl cellulose and styrene-butadiene rubber mixed in equal weight ratio.

[0026] The fifth technical solution of the present invention: provides a potassium ion battery, the raw materials of which include the above-mentioned potassium ion battery negative electrode.

[0027] Furthermore, the potassium ion battery raw materials include: a positive electrode, an electrolyte and the above-mentioned potassium ion battery negative electrode.

[0028] Preferably, the electrolyte includes: an electrolyte with a concentration of 0.8 M obtained by dissolving KFP6 in a mixed solvent of EC and EDC in a volume ratio of 1:1, or an electrolyte with a concentration of 1 to 5 M obtained by dissolving KFSI in DME, or an electrolyte with a concentration of 1 to 5 M obtained by dissolving KFSI in a mixed solvent of EC and EDC in a volume ratio of 1:1, more preferably an electrolyte with a concentration of 5 M obtained by dissolving KFSI in DME.

[0029] The present invention discloses the following technical effects:

[0030] The hollow carbon@zinc sulfide nanoparticles of the present invention are composed of nano hollow derived carbon and nano zinc sulfide particles. The shell thickness is precisely controlled by controlling the concentration of the etchant tannic acid. When the concentration of the etchant tannic acid is 1.45-11.64 mM, the shell thickness of the prepared hollow carbon@zinc sulfide nanoparticles is 45-90 nm.

[0031] The present invention realizes a method for synthesizing hollow carbon@zinc sulfide nanoparticles with highly controllable shell thickness. The material preparation method does not require the addition of a template, has a simple process, mild reaction conditions, and can accurately control the shell thickness.

[0032] The hollow carbon@zinc sulfide nanoparticles prepared by the present invention can be used for efficient potassium storage at room temperature and high temperature of 60°C. The unique cavity pore structure of the hollow carbon@zinc sulfide nanoparticles not only effectively alleviates the deformation of the electrode material and provides additional energy storage sites, thereby achieving high cycle stability and high reversible specific capacity; it can also promote the penetration of electrolytes and the transmission of potassium ions, achieving excellent rate performance. At room temperature, the hollow carbon@zinc sulfide nanoparticles with a shell thickness of 60nm exhibited excellent comprehensive potassium storage performance: at 30mAg -1 The reversible specific capacity is as high as 415 mAh g -1 , at 2.0Ag -1 The reversible specific capacity at the current density is 167 mAh g -1 , at 2.0Ag -1 After 1100 cycles at the current density, the capacity retention rate is close to 100%. At a high temperature of 60°C, the hollow carbon@ZnS nanoparticles with a shell thickness of 75nm show excellent comprehensive potassium storage performance: at 30mAg -1 The reversible specific capacity is as high as 450 mAh g -1 , at 5.0Ag -1 The reversible specific capacity at the current density is 207 mAh g -1 , at 1.0Ag -1 After 450 cycles at the same current density, the capacity is 320 mAh g -1 The capacity retention rate is 88.6%; the specific capacity, rate performance and cycle performance are better than the publicly available potassium ion battery negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1It is a process flow chart of an embodiment in a specific embodiment of the present invention;

[0035] Figure 2 This is a transmission electron microscopy image of hollow carbon@zinc sulfide nanoparticles with a shell thickness of 45 nm prepared in Example 1;

[0036] Figure 3 This is a transmission electron microscopy image of the hollow carbon@zinc sulfide nanoparticles prepared in Example 2;

[0037] Figure 4 This is a transmission electron microscopy image of hollow carbon@zinc sulfide nanoparticles with a shell thickness of 60 nm prepared in Example 2;

[0038] Figure 5 A high-resolution transmission electron micrograph of the hollow carbon@zinc sulfide nanoparticles prepared in Example 2 and its corresponding element distribution diagram;

[0039] Figure 6 This is a transmission electron micrograph of hollow carbon@zinc sulfide nanoparticles with a shell thickness of 75 nm prepared in Example 3;

[0040] Figure 7 This is a transmission electron microscopy image of hollow carbon@zinc sulfide nanoparticles with a shell thickness of 90 nm prepared in Example 4;

[0041] Figure 8 Transmission electron microscopy image of the carbon@zinc sulfide composite prepared in Comparative Example 1;

[0042] Fig. 9 XRD diagrams of the hollow carbon@zinc sulfide nanoparticles prepared in Examples 1 to 4 and the carbon@zinc sulfide composite prepared in Comparative Example 1;

[0043] Fig.10 The potassium ion battery prepared in Example 6 is 30mAg -1 The first cycle charge and discharge curve at the current density of;

[0044] Fig.11 The potassium ion battery prepared in Example 6 is 1.0Ag -1 Schematic diagram of the cycling performance after 200 cycles at the current density;

[0045] Fig.12 The potassium ion battery containing the hollow carbon@zinc sulfide nanoparticles of Example 2 in Example 6 is subjected to 2.0Ag -1 Schematic diagram of the cycle performance after 1100 cycles;

[0046] Fig.13 The potassium ion battery prepared in Example 6 is 0.03-2.0Ag -1Rate performance diagram under current density conditions;

[0047] Fig.14 The potassium ion battery prepared in Example 6 was heated at 60°C and 30 mA. -1 The first cycle charge and discharge curve at the current density of;

[0048] Fig.15 The potassium ion battery prepared in Example 6 was heated to 60°C and 1.0Ag. -1 Schematic diagram of cycling performance under current density;

[0049] Fig.16 The potassium ion battery prepared in Example 6 is heated to 60°C and 0.03-5.0Ag. -1 Rate performance diagram at different current densities. DETAILED DESCRIPTION

[0050] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0051] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0052] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0053] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0054] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0055] In a specific embodiment of the present invention, the preparation step of the zeolite imidazole framework (ZIF-8) nanoparticles used includes: dissolving 2-methylimidazole and a metal zinc salt in a methanol solvent at a molar ratio of 1:0.1 to 1 for reaction to prepare zeolite imidazole framework (ZIF-8) nanoparticles, and the metal zinc salt includes: one of zinc sulfate, zinc chloride or zinc nitrate, wherein the specified zinc sulfate, zinc chloride or zinc nitrate includes its corresponding hydrate.

[0056] At the same time, zeolite imidazole framework (ZIF-8) nanoparticles can also be commercially available products without affecting the realization of the technical effects.

[0057] Unless otherwise specified, the room temperature or normal temperature mentioned in the specific embodiments of the present invention refers to 20-30°C.

[0058] Figure 1 This is a process flow chart of an example in a specific embodiment of the present invention. The present invention adjusts the shell thickness in the selective etching stage to prepare hollow carbon@zinc sulfide nanoparticles with different shell thicknesses.

[0059] Example 1

[0060] The preparation steps of hollow carbon@ZnS nanoparticles with a shell thickness of 45 nm are as follows:

[0061] S1. Weigh zinc nitrate hexahydrate (75 mmol) and add it to 750 mL of methanol. Weigh 2-methylimidazole (300 mmol) and add it to 125 mL of methanol. Stir each for 5 min to obtain two solutions. Pour the zinc nitrate hexahydrate methanol solution into the 2-methylimidazole methanol solution and stir for 1 min. After aging for 24 h, centrifuge, wash, and dry at 60° C. to obtain zeolite imidazole framework nanoparticles for later use.

[0062] S2, add 1.0g of zeolite imidazole framework nanoparticles to 200mL of methanol, and ultrasonically disperse for 30min to obtain a zeolite imidazole framework nanoparticle dispersion; take 0.725mmol of tannic acid and dissolve it in 300mL of methanol, stir for 5min, and obtain a tannic acid methanol solution; pour the obtained tannic acid methanol solution into the zeolite imidazole framework nanoparticle dispersion and stir for 30min, centrifuge, wash, and dry at 60°C to obtain core-shell-zeolite imidazole framework@coordination polymer nanoparticles with a core-shell structure, which are set aside; the calculation of the concentration of the tannic acid methanol solution used for etching is based on the molar amount of tannic acid used and the total volume of the mixed solution;

[0063] S3, adding 300 mg of core-shell-zeolite imidazole framework @ coordination polymer nanoparticles into 45 mL of methanol, ultrasonically dispersing for 30 min, to obtain core-shell-zeolite imidazole framework @ coordination polymer nanoparticle dispersion; taking 300 mg of thioacetamide and dissolving it in 15 mL of methanol to obtain thioacetamide methanol solution; pouring the thioacetamide methanol solution into the core-shell-zeolite imidazole framework @ coordination polymer nanoparticle dispersion, stirring for 5 min, and then transferring to a reactor at 90° C. to react for 3 h; then centrifuging, washing, and drying at 60° C. to obtain hollow-tannic acid @ zinc sulfide nanoparticles with a hollow structure;

[0064] S4. The hollow-tannic acid@zinc sulfide nanoparticles were placed in a tubular furnace filled with Ar atmosphere and heat treated at 500°C for 3 hours to obtain hollow carbon@zinc sulfide nanoparticles with a hollow structure and a shell thickness of 45 nm.

[0065] Figure 2 This is a transmission electron microscope image of the hollow carbon@zinc sulfide nanoparticles with a shell thickness of 45 nm prepared in Example 1. It can be seen that there is a hollow cavity inside the nanoparticles, and the hollow shell thickness is 45 nm.

[0066] Example 2

[0067] The preparation steps of hollow carbon@ZnS nanoparticles with a shell thickness of 60 nm are as follows:

[0068] Compared with Example 1, the only difference is that the amount of etchant tannic acid used is 1.45 mmol, and the concentration of the tannic acid methanol solution used for etching is 2.91 mM.

[0069] Figure 3 This is a transmission electron microscope image of the hollow carbon@zinc sulfide nanoparticles prepared in Example 2. Figure 4 This is a transmission electron micrograph of hollow carbon@zinc sulfide nanoparticles with a shell thickness of 60 nm prepared in Example 2. Figure 3 and Figure 4 It can be seen that there is a hollow cavity inside, and the thickness of the hollow shell is 60nm.

[0070] Figure 5 This is a high-resolution transmission electron micrograph of the hollow carbon@zinc sulfide nanoparticles prepared in Example 2 and its corresponding element distribution diagram. It can be seen that the C, N, O, S and Zn elements are uniformly distributed in the hollow carbon@zinc sulfide nanoparticles prepared in the present invention.

[0071] Example 3

[0072] The preparation steps of hollow carbon@ZnS nanoparticles with a shell thickness of 75 nm are as follows:

[0073] Compared with Example 1, the only difference is that the amount of etchant tannic acid used is 2.91 mmol, and the concentration of the tannic acid methanol solution used for etching is 5.82 mM.

[0074] Figure 6 This is a transmission electron micrograph of the hollow carbon@zinc sulfide nanoparticles with a shell thickness of 75 nm prepared in Example 3. It can be seen that there is a hollow cavity inside the nanoparticles, and the hollow shell thickness is 75 nm.

[0075] Example 4

[0076] Compared with Example 1, the only difference is that the amount of etchant tannic acid used is 5.82 mmol, and the concentration of the tannic acid methanol solution used for etching is 11.64 mM.

[0077] Figure 7 This is a transmission electron micrograph of the hollow carbon@zinc sulfide nanoparticles with a shell thickness of 90 nm prepared in Example 4. It can be seen that there is a hollow cavity inside the nanoparticles, and the hollow shell thickness is 90 nm.

[0078] Fig. 9 The XRD patterns of the hollow carbon@zinc sulfide nanoparticles prepared in Examples 1 to 4 and the carbon@zinc sulfide composite prepared in Comparative Example 1 show that the XRD characteristic peaks of the hollow carbon@zinc sulfide nanoparticles prepared in Examples 1 to 4 and the carbon@zinc sulfide composite prepared in Comparative Example 1 all correspond to the PDF card of cubic zinc sulfide.

[0079] Comparative Example 1:

[0080] The preparation steps of carbon@zinc sulfide composite are:

[0081] Compared with Example 1, the only difference is that the preparation process does not include the selective etching step of S2, and the zeolite imidazole framework nanoparticles obtained in S1 are directly used to perform the sulfurization step in S3, followed by the heat treatment step in S4.

[0082] Figure 8 This is a transmission electron microscope image of the carbon@zinc sulfide composite prepared in Comparative Example 1. It can be seen that it presents a solid particle structure.

[0083] Example 5

[0084] The preparation steps of the negative electrode sheet of potassium ion battery are as follows:

[0085] S1. The hollow carbon@zinc sulfide nanoparticles prepared in Examples 1 to 4 or the carbon@zinc sulfide composite prepared in Comparative Example 1 are used as negative electrode materials, and are mixed evenly with a conductive agent Super P and a binder (a mixture of sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 1:1) in a ratio of 70:20:10, and then deionized water is added and mechanically stirred to obtain a uniform slurry;

[0086] S2. The slurry is coated on a copper foil and dried under vacuum conditions for not less than 12 hours to obtain a negative electrode sheet for a potassium ion battery.

[0087] Example 6

[0088] The preparation steps of potassium ion battery are:

[0089] S1. Cut the negative electrode sheet of the potassium ion battery prepared in Example 5 into a circular electrode sheet with a diameter of 10 mm;

[0090] S2. The circular electrode sheet obtained in step S1 is used as the negative electrode of the potassium ion battery, the glass fiber membrane is used as the separator of the battery, 5M KFSIDME is used as the electrolyte, and it is assembled with metallic potassium into a button battery. The specification of the button battery is CR2032.

[0091] Effect Example 1

[0092] Before testing the potassium ion battery, it needs to be left at room temperature for more than 12 hours to ensure that the electrolyte is completely penetrated. Then, a battery charge and discharge tester is used to perform a constant current charge and discharge test on the battery prepared in Example 6. The test voltage range is 0.01-3.0V, and the temperature of the test environment is 25°C.

[0093] Fig.10 The potassium ion battery prepared in Example 6 is 30mAg -1 The first cycle charge and discharge curve at the current density is shown in Figure 2. Fig.10 It can be seen that the reversible capacity of the first cycle of the potassium ion battery prepared by the hollow carbon@zinc sulfide nanoparticles of Examples 1 to 4 is 424 mAh g -1 , 415mAh g -1 , 380mAh g -1 and 329mAh g -1 The reversible capacity of the first cycle of the potassium ion battery prepared from the carbon@zinc sulfide composite of Comparative Example 1 is 428 mAh g -1 .

[0094] Fig.11 The potassium ion battery prepared in Example 6 is 1.0Ag -1 Schematic diagram of the cycle performance after 200 cycles at the current density, Fig.11It can be seen that the capacity retention rates of Examples 2-4 are close to 100%, while the capacity retention rate of Example 1 is 59%, and the capacity retention rate of Comparative Example 1 is only 29%.

[0095] Fig.12 The potassium ion battery containing the hollow carbon@zinc sulfide nanoparticles of Example 2 in Example 6 is subjected to 2.0Ag -1 Schematic diagram of the cycle performance after 1100 cycles, Fig.12 It can be seen that its cycle capacity retention rate is close to 100%, which has very excellent cycle performance.

[0096] Fig.13 The potassium ion battery prepared in Example 6 is 0.03-2.0Ag -1 The rate performance diagram under current density conditions is given by Fig.13 It can be seen that in 2Ag -1 At a current density of 1.34 W, the specific capacity of Examples 1 and 2 is as high as 193 mAh g -1 and 167mAh g -1 , while the specific capacities of Examples 3 and 4 are 78 and 58 mAh g -1 The specific capacity of comparative example 1 is only 46 mAh g -1 It can be seen that the hollow carbon@zinc sulfide nanoparticles with a shell thickness of 60 nm prepared in Example 2 have the best comprehensive battery performance as the negative electrode of potassium ion battery at room temperature.

[0097] Effect Example 2

[0098] Before testing the potassium ion battery, it is necessary to stand at room temperature for more than 12 hours to ensure that the electrolyte is completely penetrated, and then placed at a high temperature of 60°C for 2 hours to allow the battery to fully heat up to the test temperature. A battery charge and discharge tester is used to perform a constant current charge and discharge test on the battery prepared from the materials of Examples 1 to 4 in this Example 6. The test voltage range is 0.01-3.0V, and the temperature of the test environment is 60°C.

[0099] Fig.14 The potassium ion battery prepared in Example 6 was heated at 60°C and 30 mA. -1 The first cycle charge and discharge curve at the current density is shown in Figure 2. Fig.14 It can be seen that the reversible capacity of the first cycle of the potassium ion battery prepared by the hollow carbon@zinc sulfide nanoparticles of Examples 1 to 4 is 493 mAh g -1 , 471mAh g -1 , 450mAh g -1 and 414mAh g -1 .

[0100] Fig.15The potassium ion battery prepared in Example 6 was heated to 60°C and 1.0Ag. -1 Schematic diagram of the cycling performance under current density. Fig.15 It can be seen that the capacity of the potassium ion battery containing hollow carbon@zinc sulfide nanoparticles in Example 1 decays rapidly, and Example 2 begins to decay significantly after only 50 cycles, while Examples 3 and 4 can be stably cycled for more than 300 cycles. Among them, the capacity of Example 3 is still 320 mAh g after 450 cycles. -1 , the capacity retention rate is 88.6%.

[0101] Fig.16 The potassium ion battery prepared in Example 6 is heated to 60°C and 0.03-5.0Ag. -1 The rate performance diagram under current density. Fig.16 It can be seen that in 3Ag -1 and 5Ag -1 At a current density of 1.34 W, the specific capacity of Example 3 is as high as 266 mAh g -1 and 207mAh g -1 .

[0102] It can be seen that the hollow carbon@zinc sulfide nanoparticles with a shell thickness of 75 nm prepared in Example 3 have the best comprehensive battery performance as the negative electrode of the potassium ion battery at a high temperature of 60°C.

[0103] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a hollow carbon@zinc sulfide negative electrode material for a potassium ion battery, characterized in that the steps include: Using tannic acid methanol solution to selectively etch zeolite imidazole framework nanoparticles to obtain core-shell-zeolite imidazole framework@coordination polymer nanoparticles; the zeolite imidazole framework nanoparticles are ZIF-8 nanoparticles; wherein, during the selective etching process, tannic acid forms a coating layer on the surface of ZIF-8 and releases protons to etch the inner layer of ZIF-8, thereby forming a yolk-eggshell structure; The core-shell-zeolite imidazole framework@coordination polymer nanoparticles are vulcanized with thioacetamide to obtain hollow-tannic acid@zinc sulfide nanoparticles; The hollow-tannic acid@zinc sulfide nanoparticles are subjected to heat treatment under an inert atmosphere to obtain the hollow carbon@zinc sulfide negative electrode material; The mass ratio of the tannic acid to the zeolite imidazole framework nanoparticles is 1.25-10:1; the concentration of the tannic acid methanol solution is 1.45-11.64 mM; The mass ratio of thioacetamide to core-shell-zeolite imidazole framework@coordination polymer nanoparticles is 0.5-2:1; The vulcanization temperature is 80-120°C; The inert atmosphere includes: one of a nitrogen atmosphere, an argon atmosphere or a helium atmosphere; The heat treatment temperature is 400-900°C, the heating rate is 1-20°C / min, and the heat preservation time is 1-10 h.

2. A hollow carbon@zinc sulfide negative electrode material prepared by the preparation method as claimed in claim 1.

3. Use of the hollow carbon@zinc sulfide negative electrode material according to claim 2 in a potassium ion battery.

4. A potassium ion battery negative electrode, characterized in that Including the hollow carbon@zinc sulfide negative electrode material as described in claim 2.

5. A potassium ion battery, characterized in that: Comprising the potassium ion battery negative electrode as described in claim 4.

Citation Information

Patent Citations

  • Preparation method of MOF-5 containing three carboxyl functional groups and application of MOF-5 in high-temperature potassium ion battery

    CN113948699A

  • Self-supporting nitrogen-doped carbon / ZnS flexible composite material as well as preparation method and application thereof

    CN116282130A